KONSTRUKSI IDENTITAS TOKOH DALAM AU BONHEUR DES OGRES KARYA DANIEL PENNAC - Mutmainnah Mutmainnah; Ade Yolanda Latjuba; Hasbullah Hasbullah (JURNAL ILMU BUDAYA, 2022)
This research will explain the identity of Benjamin obtained based on the construction of people by looking at the background of his life and work. The theory used in this study is the intrinsic theory of literature, which includes figures and characterizations as well as social settings and identity. The research reveals two sides of the views of people around the character.This resulted in three things, namely (1) a description of Benjamin's family life that views him as a good, understanding and responsible person, (2) a description of Benjamin's work and relationships with his colleagues which makes him a scapegoat and also a suspect in a case bombing that occurred at his workplace, (3) Benjamin's identity was constructed based on the views of those around him.